Investigation on pullout strength between different design of cannulated pedicle screw and osteoporosis bones to obtain an optimum design - Daud, Rosdi; A., Asyraf; Hassan, Mas Ayu; A., Shah; Tomadi, Dr. Siti Haryani (The Mattingley Publishing Co., Inc., 2020)
Cannulated Pedicle Screw (CPS) is the tools implemented in the biomedical sector to strengthen the structure of the bones and to increase the pullout strength in osteoporotic patients. The cement is injected from the top of cannulated screw to bone which the radial hole plays the main role in ensuring uniform cement distribution to bone for the enhanced fixation between CPS and bone, leading to higher pullout strength. This paper is aim to investigate on pullout strength between different design of cannulated pedicle screw and osteoporosis bones to obtain an optimum design of CPS in focusing on its radial holes. Four designs were constructed using SolidWorks software where one of it is the current model of CPS with 2 radial holes, 1.5 mm diameter whereas the proposed design 1 with 1 radial holes-1 slot, design 2 with 1 double radial hole-1 slot and design 3 with 1 double radial hole and 1 double slot. ANSYS software is used for the Finite Element Analysis (FEA). The Finite Element Models were verified with the previous research FEA result. The FEA results of stress von mises for current and proposed design were then compared to investigate their pullout strength whereby the yield strength of CPS is 820 MPa and 130MPa for osteoporosis bone. The FEA results show 19.26 MPa maximum stresses for the current design and 18.69 MPa, 22.3 MPa and 22.48 MPa for proposed design 1, 2 and 3 respectively. Thus, the current Cannulated Pedicle Screw seem can be improved by the proposed design 1 which is with 1 radial hole (1.5 mm) and 1 slot (1.5 mm x 3 mm) due to its gain the lowest average maximum stress. It can be concluded that the pullout strength of the Cannulated Pedicle Screw were not depends directly on how many the number of radial hole/slot in improving pullout strength since the single hole and slot is considered the optimum design of CPS due to its lowest average of maximum stress on the critical region.